2016
DOI: 10.1002/ccd.26442
|View full text |Cite
|
Sign up to set email alerts
|

Association between health status and long‐term mortality after percutaneous revascularization of peripheral artery disease

Abstract: Among patients with symptomatic PAD undergoing EVT, improvement of PAD-specific health status at 1 year follow-up was associated with improved long-term survival. Whether additional treatment for patients with poor response to EVT could improve long-term survival warrants further investigation. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Several studies have indicated that diabetes is a predictor of poor outcomes following such procedures with poorer patency rates 8 and cardiovascular outcomes. 9,10 However, other studies suggested that diabetics have similar outcomes to nondiabetics following stenting 11 or atherectomy (directional 12 or rotational 13 ) despite more advanced comorbidities. In these studies, and after adjusting for multiple comorbidities, diabetics had a similar patency rate, freedom from target lesion revascularization and clinical improvement compared with nondiabetics.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that diabetes is a predictor of poor outcomes following such procedures with poorer patency rates 8 and cardiovascular outcomes. 9,10 However, other studies suggested that diabetics have similar outcomes to nondiabetics following stenting 11 or atherectomy (directional 12 or rotational 13 ) despite more advanced comorbidities. In these studies, and after adjusting for multiple comorbidities, diabetics had a similar patency rate, freedom from target lesion revascularization and clinical improvement compared with nondiabetics.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when successful, the revascularization procedure in PAD patients, in addition to improving functional status, significantly reduces the occurrence of future major cardiovascular events by approximately four times [ 35 ]. Moreover, the revascularization procedures, enhancing patients’ mobility [ 36 ], improved their prognosis and survival probability at the intermediate PAD stages [ 37 , 38 ], although not in patients with critical limb ischemia [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the obvious reduced functional capacity, PAD patients experience high rates of cardiovascular (CVD) morbidity and mortality, especially those with chronic, low-grade inflammation, such as diabetes mellitus and obesity [ 2 ]. Revascularization of lower-limb arteries has been associated with better long-term survival and quality of life when the patency of the arteries is maintained [ 3 ]. However, the restenosis rate and the post-intervention occurrence of major adverse cardiovascular events (MACE) is still high despite the advances in revascularization techniques and the optimal pharmaceutical therapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%